Surface colonization and subsequent development of infections with multi drug resistant organisms in a neonatal intensive care unit - Mary Dias; Juveyriya Saleem (BMC, 2019)
Abstract Background This study analyzes colonization of the neonates in a NICU and incidence of these colonized infants developing infections due to the colonizers. Methods Over a 12 month period, samples (surface swabs and rectal swabs) were obtained from all the infants admitted to NICU. The samples were cultured and examined for the presence of colonizers and especially for multi-drug resistant organisms. Results From the total 533 patients, 473 (89%) neonates acquired colonizers and 60 (11%) did not. Of the 473 (89%) colonized infants, 57 (12%) developed infections of whom 33 (58%) were infected from the same organism as the colonizer and 24 (42%) neonates developed an infection that was different from the colonizer. 416 (88%) infants did not develop any infection inspite of being colonized. Conclusions The total numbers of babies contracting infection were more in the colonized group than the non-colonized. Other factors like gestational age and preterm may have played a role in development of infection in addition to colonization in these babies. Screening for the presence of MDRO colonization may be of limited use in predicting infections in the colonized individual. However, knowledge of their presence results in implementation of strict infection control practices. This along with judicious uses of antimicrobials effectively reduces infections from colonized bacteria and more importantly prevent their spread.